Neuropsychological morbidity in the First Seizure Clinic: Prominent mood symptoms and memory issues in epilepsy - Remy Pugh; David N. Vaughan; Graeme D. Jackson; Jennie Ponsford; Chris Tailby (Epilepsia Open)
Abstract Objective To examine the neuropsychological morbidity across the spectrum of patients presenting to a First Seizure Clinic, and test the hypothesis that cognitive and psychological compromise is especially prominent in those diagnosed with epilepsy. Methods A sample of 201 patients referred to the Austin Hospital First Seizure Clinic (FSC) underwent cognitive screening via telephone and psychological screening via online questionnaire, all prior to their diagnostic evaluation (and any attendant treatment recommendation) at the FSC. Rates of cognitive (i.e., scores <10th percentile) and psychological impairment (using established clinical cut scores) were compared against 35 demographically matched controls. Cognitive differences were explored between the most frequently encountered patient subgroups (epilepsy, n = 48; first unprovoked seizure, n = 24; acute symptomatic seizure, n = 24; syncope, n = 35) via a multivariate analysis of variance, with diagnostic labels applied retrospectively after a period of follow‐up. Results People with epilepsy were most likely to show cognitive impairments, particularly in learning and memory, with performances worse than all other FSC groups (F [3127] = 2.44, p = 0.03). Clinically significant depressive symptoms were similarly prevalent in all patient groups, with one in three at risk for Major Depressive Disorder. Elevated anxiety symptoms were common across patient groups; however, not significantly different to controls. Significance Cognitive impairment in epilepsy and mood problems in all FSC groups are detectable via remote screening as early as the first seizure. Learning and memory difficulties are particularly prevalent in new‐onset epilepsy and may lend diagnostic information when paired with clinical factors. Plain Language Summary This study explored cognitive and psychological differences between various patient groups attending an Australian First Seizure Clinic. We found that learning and memory abilities were poorer in people with epilepsy than other patient groups including those with non‐epileptic seizures, and seizure‐mimics (fainting episodes). Therefore, along with standard epilepsy investigations, memory performances could help to predict which patients have epilepsy versus a non‐epileptic condition after a first suspected seizure. Further, approximately one in three from each patient group showed high symptoms of depression and anxiety. The findings highlight the importance of evaluating cognition and mood in people with first seizures.